2018
DOI: 10.1186/s13008-018-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Subunits of human condensins are potential therapeutic targets for cancers

Abstract: The main role of condensins is to regulate chromosome condensation and segregation during cell cycles. Recently, it has been suggested in the literatures that subunits of condensin I and condensin II are involved in some human cancers. This paper will first briefly discuss discoveries of human condensins, their components and structures, and their multiple cellular functions. This will be followed by reviews of most recent studies on subunits of human condensins and their dysregulations or mutations in human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 105 publications
2
18
0
Order By: Relevance
“…9B ). The condensin complex has been suggested as a potential therapeutic target for cancer [138], and human homologs YCG1/NCAPG2 , YCS4/NCAPD2 , and SMC4/SMC4 are synthetic lethal with the Ras oncogene [124].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9B ). The condensin complex has been suggested as a potential therapeutic target for cancer [138], and human homologs YCG1/NCAPG2 , YCS4/NCAPD2 , and SMC4/SMC4 are synthetic lethal with the Ras oncogene [124].…”
Section: Resultsmentioning
confidence: 99%
“…TMA22/DENR also exerts evolutionarily conserved influence on telomeric function and cell proliferation [215]. YCG1/NCAPG and SMC2/SMC2 are components of the condensin complex, which are overexpressed in cancer [138]. NUP170/NUP155 , which functions in telomere tethering at the nuclear periphery ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Defective mitotic chromosome assembly is clinically relevant. Dysregulation of condensin complex I and II are both associated with poor prognosis and are gaining attention as potential therapeutic targets (Wang, Yang, Li, & Cao, 2018). High nCAP-D2 expression is associated with increased metastasis and decreased survival in triple negative breast cancer (Y.…”
Section: Discussionmentioning
confidence: 99%
“…One defect in subunits of condensin causes incomplete chromosome condensation . Thus, condensins could be a therapeutic target for human cancers . A recent report showed that NCAPH is upregulated in colon cancer tissue, and its high expression correlates with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…31 Thus, condensins could be a therapeutic target for human cancers. 32 A recent report showed that NCAPH is upregulated in colon cancer tissue, and its high expression correlates with poor prognosis. Furthermore, inhibiting NCAPH promotes cell apoptosis and cell cycle arrest at the G2/M phase, and exerts antitumor effects in colorectal cancer in vitro and in vivo.…”
Section: Chka Cdc6 Ncaphmentioning
confidence: 99%